Vulnerability assessment of Sog Bridge’s lead rubber bearing pads - Evan Lloyd Greene 1995- (2024)
This thesis examines the seismic vulnerability of base isolating lead rubber bearings (LRBs) on the Sog Bridge, a vital link for towns northeast of the Sog River in the South Iceland seismic zone. Due to its proximity to major fracture zones, the bridge frequently experiences significant seismic activity. A scenario-based seismic assessment based on GMPEs developed from informative priors revealed that the 2008 Ölfus and 2000 Hestfjall earthquakes produced peak ground accelerations of 0.42 g and 0.22 g, respectively, at the bridge site. Given prior history of intense shaking LRBs play a critical role in the seismic performance of vital structures like bridges. Therefore, assessing the seismic performance of the lead rubber bearings is crucial. Fragility curves for the bearings were developed using response parameters from existing literature to define damage states and incremental dynamic analysis based on seven earthquake time histories. These analyses were conducted using a finite element model in SAP2000, supplemented by detailed modeling in AutoCAD. The analysis showed that the bridge is likely to exceed the minor and moderate damage states for pounding at relatively low shaking levels such as 0.25 g. Shear displacements in the bearings surpassed the spacing between the superstructure and abutments. These findings emphasize the need for enhanced seismic resilience measures for the Sog Bridge. Vegagerðin